A flexible metal–organic framework with a high density of sulfonic acid sites for proton conduction. Issue 11 (November 2017) - Yang, Fan; Xu, Gang; Dou, Yibo; Wang, Bin; Zhang, Heng; Wu, Hui; Zhou, Wei; Li, Jian-Rong; Chen, Banglin
Abstract The design of stable electrolyte materials with high proton conductivity for use in proton exchange membrane fuel cells remains a challenge. Most of the materials explored have good conductivity at high relative humidity (RH), but significantly decreased conductivity at reduced RH. Here we report a chemically stable and structurally flexible metal–organic framework (MOF), BUT-8(Cr)A, possessing a three-dimensional framework structure with one-dimensional channels, in which high-density sulfonic acid (–SO3 H) sites arrange on channel surfaces for proton conduction. We propose that its flexible nature, together with its –SO3 H sites, could allow BUT-8(Cr)A to self-adapt its framework under different humid environments to ensure smooth proton conduction pathways mediated by water molecules. Relative to other MOFs, BUT-8(Cr)A not only has a high proton conductivity of 1.27 × 10−1 S cm−1 at 100% RH and 80 °C but also maintains moderately high proton conductivity at a wide range of RH and temperature. Proton-conducting metal-organic frameworks (MOFs) could be used as the electrolytes in proton exchange membrane fuel cells but chemically stable materials that perform well at low humidity are still sought. Here the authors prepare a stable, structurally flexible MOF that maintains high proton conductivity under a wide range of humidity.